Probiotics ameliorate H. pylori-associated gastric β-catenin and COX-2 carcinogenesis signaling by regulating miR-185 - Yao-Jong Yang; Chung-Tai Wu; Hsiu-Chi Cheng; Wei-Ying Chen; Joseph T. Tseng; Wei-Lun Chang; Bor-Shyang Sheu (Journal of Biomedical Science)
Abstract Background This study aimed to investigate whether probiotics can ameliorate the H. pylori-induced Wnt/β-catenin-related COX-2 carcinogenesis signaling pathway by regulating the expression of microRNAs (miRNAs). Methods An H. pylori isolate and GES-1 cells were used to establish a COX-2-associated carcinogenesis axis. Western blot analysis was conducted to investigate Wnt/β-catenin and COX-2 signaling. Next-generation sequencing and DIANA Tools identified significant differences in miRNA expressions. The probiotics Lactobacillus acidophilus and Bifidobacterium lactis were used to study anti-carcinogenesis effects in GES-1 and miRNA-transfected GES-1 cells. The H. pylori-infected patients with intestinal metaplasia (IM) were randomly allocated into probiotic treatment or not after successful eradication, the IM regression was assessed by the 2nd esophagogastroduodenoscopy one year after treatment. Results Pretreatment with probiotics significantly reduced H. pylori-induced nuclear β-catenin phosphorylation and COX-2 levels in GES-1 cells. Among 9 significantly altered miRNAs, miR-185 was the only miRNA targeting the Wnt/β-catenin signaling pathway. H. pylori increased miR-185 expression and upregulated COX-2 carcinogenesis through the Wnt/β-catenin pathway, but not the JAK2/STAT3 pathway. B. lactis ameliorated H. pylori-induced miR-185 expression and nuclear β-catenin/COX-2 signaling in a dose-dependent manner. In the 6-month probiotic-treated patients had a significantly higher IM regression rate than controls (intention-to-treat: 37.5 vs 11.5%, OR: 4.60, 95% CI: 1.134–18.65, p = 0.025; per-protocol: 46.2 vs 17.6%, OR: 4.00, 95% CI: 0.923–17.33, p = 0.055). Patients without IM regression had significantly higher miR-185 levels in follow-up biopsies (p < 0.01). Conclusions Pretreatment with B. lactis ameliorated the H. pylori-induced COX-2 carcinogenesis pathway by reducing miR-185 expression, which targets Wnt/β-catenin signaling. (ClinicalTrials.gov, NCT05544396).